PATHOGENETIC MECHANISMS OF EXPERIMENTAL GINGIVITIS PROGRESSION UNDER THE INFLUENCE OF LIPOPOLYSACCHARIDE - Sokolova, I.I.; Skydan, K.V.; Skydan, M.I.; Levitskiy, A.P.; Slynko, Y.A. (World of Medicine and Biology, 2019)
The paper presents the results of patogenetic rationale for the use of gel with lipopolysaccharide for gingivitis modelling. It shows, that lipopolysaccharide applications lead to significant increase in activity of elastase by 26.8%, malonic dialdehyde by 32.8%, urease by 78.9%, degree of dysbiosis by 32.6%, decrease in activity of lysozyme by 57.6% and antioxidant-prooxidant index by 29.7%. Thus, lipopolysaccharide application leads to the progression of inflammation processes in gums of experimental animals, dysbiosis and oxidative stress, that is pathogenetic links of gingivitis progression in humans as well.